Young people’s knowledge, attitude, and behaviour on STI/HIV/AIDS in the context of Nepal: A systematic review - Upreti, D; Regmi, P; Pant, P; Simkhada, P (Kathmandu University Medical Journal, 2010)
Background: Sexual and reproductive health of young people has become a major health problem in recent decades. Recent and rapidly increasing Human Immune Deficiency Virus (HIV) rates show an urgent need for Sexually Transmitted Infections (STIs) and HIV prevention interventions in Nepal. Objectives: This paper attempts to assess knowledge, attitude and behaviour on STIs/HIV/AIDS in the context of young peoples of Nepal. Materials and methods: A systematic review based on the available literature was carried out including both qualitative and quantitative studies. Results: Our findings indicate that the overall knowledge regarding STIs and HIV/AIDS is high although the level of knowledge seems to differ according to education, gender, and area of residence. Knowledge about condoms was also very high but practice of correct and consistent use in premarital and extramarital sexual relations with non-regular partners seems to be lower. The overall sexual behaviour among young people is unsafe. Conclusion: This suggests that young people's sexual and reproductive health issues need to be further addressed and explored in order to promote safer and responsible sexual behaviour. Key words: Attitude; Behaviour; HIV/AIDS; Knowledge; Nepal; STIs; Systematic Review; Young people DOI: 10.3126/kumj.v7i4.2759 Kathmandu University Medical Journal (2009) Vol.7, No.4 Issue 28, 383-391